Principles of Law in the Legal System of Lithuania: Determining or Directing? - Lastauskienė, Giedrė (Vilnius University Open Series, 2024)
The identification and description of the principles of Law and their place in the legal system are discussed in the article. The goal of this paper is to review the changes of perception of the principles of Law in Lithuania during the period of the paradigm change, after the restoration of the independence of Lithuania. The practice formed by the Constitutional Court of the Republic of Lithuania, with the court applying the principle of the rule of Law, is used for illustration of the present research.
Keywords: principles of law; legal norms; legal system; constitutional principle of the rule of law